Low-density lipoprotein cholesterol mediates the causal association between systemic lupus erythematosus and asthma: a mediation mendelian randomization study - Hui Yin; Tongxia Wang; Lin Liu; Zhi Hu (BMC Rheumatology)
Abstract Background It is well-documented that systemic lupus erythematosus (SLE) is associated with asthma. However, the causal relationship between SLE and asthma, and the potential mediator need to be explained. This study aims to confirm the cause-and-effect relationship between SLE and asthma, and evaluate the mediation effect of lipid in European ancestry. Methods A Two-sample Mendelian randomization (MR) study was applied to analyze the causal relationships between SLE and asthma. A two-step MR design was used to explore whether low-density lipoprotein cholesterol (LDL-C) mediates the causal pathway from SLE to asthma outcome. Cochran’s Q statistic methods and MR-Egger regression were used to assess heterogeneity and pleiotropy. Leave-one-out (LOO) sensitivity test was adopted to estimate the effect of removing one of the selected individual SNPs on the overall results. Funnel and forest plots were also conducted to detect the pleiotropy directly. Results SLE was significantly associated with higher asthma risk according to inverse-variance weighted (IVW) method [OR (95%CI): 1.093 (1.024–1.166)] (P = 0.007), MR Egger method [OR (95%CI): 1.192 (1.077–1.319)] (P = 0.028) and Maximum likelihood [OR (95%CI): 1.094 (1.036–1.155)] (P = 0.001), which were robust across adequate sensitivity analysis. On the contrary, asthma has no causal relationship with SLE. In addition, LDL-C may mediate a proportion of 6.15% of the total effect between SLE and asthma. Conclusion This study demonstrates that patients with SLE may have a higher risk of developing asthma, which may be mediated by LDL-C. Understanding this relationship provides insight into potential mechanisms underlying asthma development in SLE patients and offers a foundation for developing targeted treatment strategies to manage these risks effectively.